Membaca Jejak Proses Kreatif Penyair Nusa Tenggara Timur, John Dami Mukese - Yohanes Sehandi; Alexander Bala (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This article explores the poet John Dami Mukese's creative process in creating his poetry. John Dami Mukese is an Indonesian poet born in Flores, a Catholic priest who wrote about 250 poems. This study uses an expressive approach, which is an approach that emphasizes the study of literary authors. The method used is the codification method, which is the observation method by tracing the colophon in each poem. Colophons are notes at the end of a text that informs the author's place, time, and name. The analysis used is a qualitative analysis by describing the poet's creative process in creating his poetic works. The study results show that the creative process of poet John Dami Mukese began at the age of 27 years, namely, in 1977. The first three years (1977-1979) were the beginning of his creative process by finding the correct pronunciation by his personality, educational background, and profession. Over the next four years (1980-1984) was the peak period of creativity and productivity of poet John Dami Mukese in creating his poetry. From 1985 until the end of 2017, it was an anticlimax in the creative process. The poems of John Dami Mukese with religious themes based on social problems show a very deep sensitivity to the social reality that is taking place in Flores society.